Simulating the long-term labour market effects of an industrial investment.: A microsimulation approach - Lindgren, Urban (ERDKUNDE, 1999)
The aim of this article is to investigate the long-term local labour market impacts of an industrial investment. In the beginning of the 1990s the Swedish forest-based company SCA introduced a new technology for the production of high-quality paper (LWC-paper) in the Ortviken papermill, which is situated in Sundsvall (northern Sweden). The regional income injection in connection with the implementation of the investment has previously been investigated empirically by Klint and Lindgren (1992, 1993) and it was shown that a major share of the income injection trickled down locally in the municipality of Sundsvall. The ex-ante analysis of the investment’s long-term labour market effect throughout the economic life of the paper machine cannot, however, be carried out empirically. In this study the problem has been approached by means of simulation methodology and the comparisons between different possible future scenarios. The basic hypothesis is that papermills, which are resource-intensive operations and mainly compete by means of high productivity, cannot survive without high investment rates. This implies that the papermill will have to close if the upgrading of the production process is not continued. The long-term impacts are obtained by comparing a baseline scenario, in which the LWC-investment is implemented, and a counterfactual scenario of non-implementation. In order to fulfill this task, a calibrated systems model based on microsimulation methodology has been developed. The model represents the population of Sundsvall individually, i.e. it simulates future life paths of every single person in the municipality. By using micro-orientated modelling the impacts of employment reduction at the papermill can be traced to other partial local labour markets (changed unemployment levels) and to the local population (changed migration and commuting patterns). The microsimulation model is calibrated on a micro dataset that contains a number of attributes on individuals who lived or worked in the municipality at some time between 1990 and 1993 (N = 103,000). The simulation results show that there are substantial indirect labour market effects, i.e. there are many occupation categories, not related to the papermill, that meet with increased unemployment in the case of the closure of Ortviken.